2017
DOI: 10.2147/dddt.s140687
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the PD-1/PD-L1 axis for the treatment of head and neck cancer: current status and future perspectives

Abstract: Head and neck cancer (HNC) is a common malignant tumor, but traditional therapeutic methods have unsatisfactory curative effects and many complications occur. Hence, there is an urgent need to develop therapeutic methods that can elicit curative effects as well as low toxic and few side effects. With the development of cancer molecular biology and immunology, targeted therapy for immune checkpoints of programmed cell death 1 (PD-1) and programmed cell death ligand 1 (PD-L1) has shown enormous development prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 48 publications
0
35
1
Order By: Relevance
“…PD‐L1 immunoexpression in TCs and/or ICs is a useful clinical biomarker to select patients who may benefit the most from immune check‐point inhibitors. Evaluation of PD‐L1 IHC has been included as either companion or supplementary tests in multiple anti‐PD1/anti‐PD‐L1 clinical trials of various cancers . Therefore, it becomes increasingly important for practising pathologists to provide reliable and consistent interpretation of PD‐L1 IHC across different tumour types, as it is of paramount importance in determining the eligibility for anti‐PD‐L1/anti‐PD1 therapy and to predict treatment benefits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PD‐L1 immunoexpression in TCs and/or ICs is a useful clinical biomarker to select patients who may benefit the most from immune check‐point inhibitors. Evaluation of PD‐L1 IHC has been included as either companion or supplementary tests in multiple anti‐PD1/anti‐PD‐L1 clinical trials of various cancers . Therefore, it becomes increasingly important for practising pathologists to provide reliable and consistent interpretation of PD‐L1 IHC across different tumour types, as it is of paramount importance in determining the eligibility for anti‐PD‐L1/anti‐PD1 therapy and to predict treatment benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, PD‐L1 and PD‐1 have emerged as a key check‐point that can be manipulated with inhibitory monoclonal antibodies in various cancer types. Multiple prospective randomised clinical trials have shown promising results of PD‐1/PD‐L1 immune check‐point inhibitors in a variety of cancer types, including a subset of patients with urothelial carcinoma (UC), breast carcinoma (BC) and head and neck squamous cell carcinoma (HSCC), leading to the Food and Drug Administration (FDA) approval of several anti‐PD‐1/PD‐L1 agents …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of distinct immune checkpoint molecules, such as indoleamine 2,3‐dioxygenase 1 (IDO1) and programmed death‐ligand 1 (PD‐L1) in tumors, are considered as negative prognostic factors . Furthermore, immune checkpoint inhibitors, such as PD‐1/PD‐L1 axis inhibitors, are already in use as anticancer therapies . Other immune checkpoint inhibitors, such as IDO1, are still in clinical trials …”
Section: Introductionmentioning
confidence: 99%